The Impact of Human Resource Capacity on Village Institutional Resilience Moderated by Digital Transformation in Jatisari District - Majid, Amjad Abdul; Fadli, Uus MD; Rosmawati, Ery (Research in Management of Technology and Business, 2026)
Abstract This study aims to analyze the influence of human resource capacity on village institutional resilience and examine the role of digital transformation as a moderating variable in village governance in Jatisari District. The study used a quantitative approach with data collected from 104 village officials through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results showed that human resource capacity was in the good category and had a positive and significant effect on village institutional resilience, with a path coefficient value of 0.669, a T-statistic value of 12.498, and a P-value of 0.000. Meanwhile, digital transformation was descriptively in the good category, but was not proven to moderate the influence of human resource capacity on village institutional resilience, with an interaction coefficient of –0.016, a T-statistic value of 0.489, and a P-value of 0.625. These findings confirm that strengthening human resource capacity is a key factor in building village institutional resilience, while digital transformation still requires strengthening internal.